Bamlanivimab use in mild‐to‐moderate COVID‐19 disease: A matched cohort design. Issue 9 (12th August 2021) - Destache, Christopher J.; Aurit, Sarah J.; Schmidt, David; Peet Erkes, Laura; Tierney, Maureen; Vivekanandan, Renuga
Abstract: Study Objective: Our objective was to determine if bamlanivimab (LY‐CoV555; BAM), a monoclonal antibody for mild‐to‐moderate Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐Co‐V‐2, prevented emergency department (ED) visits, hospitalizations for SARS‐CoV‐2, or death within 60 days of a positive SARS‐CoV‐2 viral test. Design: Patient propensity matching was performed for BAM administration to get two discrete groups of patients; those who received BAM ( N = 117) and those who did not ( N = 117). Setting: Outpatients ( N = 2107) eligible to receive BAM from November 1 to December 31, 2020, were identified. Patients: A total of 144 of 2107 patients with mild‐to‐moderate SARS‐CoV‐2 received BAM Intervention: Eligible patients had mild‐to‐moderate SARS‐CoV‐2 disease, a positive SARS‐CoV‐2 test, and risk factor(s) for progression to severe SARS‐CoV‐2 infection. All patients were reviewed for subsequent ED visits, subsequent hospitalization, and death. Measurements and Main Results: Patients ( N = 234) were matched, 117 in each group. Median (interquartile range) age was 72 (65–80) years. Forty‐seven percent of patients were male. Twenty‐one patients who received BAM were subsequently seen in the ED compared to 34 untreated patients (18.0% vs. 29.1%; p = 0.045). Fourteen BAM‐treated patients were subsequently hospitalized post‐BAM infusion compared to 27 untreated patients (12.0% vs. 23.1%; p = 0.025). Finally, there were no mortalities in the BAM group, however, eleven patients in the untreated group died (0.0% vs. 9.4%; p < 0.001). The number needed to treat (NNT) is 11 patients to prevent one mortality event. Conclusions: BAM infusion for mild‐to‐moderate SARS‐CoV‐2 infection in outpatients significantly prevented subsequent ED visits, hospitalizations, and death from SARS‐CoV‐2.